HUMAN AND SCIENCE, LAND AND SPACE: A CASE STUDY OF “XU BING TIANSHU ROCKET” BASED ON THE ECOCRITICISM THEORY - Zhe, W; Rong, Y (Proceeding of the International Conference on Arts and Humanities, 2023)
Firstly, conceived in the field of geology, the conception of Anthropocene has now been becoming an inspiration for many artists to create their work aimed at reflecting the relationship between human beings and nature. As one of the most representative Chinses contemporary artists, Xu Bing made another bold attempt to combine aerospace with art. In 2021, a rocket was launched from Jiuquan, China, named “Xu Bing Tianshu,” the first one named after an artist and his work. The rocket could not reach outer space as expected but left an unanticipated artwork on the earth: “Xu Bing Tianshu Rocket”: Crater. Adopting the ecocriticism theory, researchers take Xu Bing’s work as a case study to examine the conflictive and inseparable interaction of Science and Art using the method of text analysis based on art reviews, interviews with the artist, and the relevant news reports. The research indicates that the launch might demonstrate the arrogance of human power, but the emergence of the “Crater,” which was considered as a symbol of failure from a scientific standpoint, presents an earth-like work of art that is out of human control and beyond human expectations, by which means the artistic expression questions anthropocentrism in a powerful way. This study would be a pioneering example of viewing space art and land art in the eyes of ecocriticism, which is expected to enrich its critical practice and contributes to a humble reflection of environmental protection